Interrater and Intrarater Reliability of Subcutaneous Echogenicity Grade and Subcutaneous Echo-Free Space Grade in Breast Cancer-Related Lymphedema - (:unkn) unknown (MARY ANN LIEBERT, INC, 2019)
Background: Subcutaneous echogenicity grade (SEG) and subcutaneous echo-free space (SEFS) grade allow semiquantitation of nonspecific subcutaneous tissue inflammation and fluid accumulation in breast cancer-related lymphedema. However, inter- and intrarater reliability of SEG and SEFS is yet to be reported. The objective of this study is to assess inter-rater and intrarater reliability of SEG and SEFS in patients with breast cancer-related lymphedema. Methods and Results: Two physiatrists performed SEG and SEFS grade to determine inter-rater and intrarater reliability. Inter-rater reliability for SEG and SEFS was excellent (Kappa [K] = 0.836, weighted Kappa [K-w] = 0.85; K = 0.884, K-w = 0.92). K and K-w values of SEG and SEFS grading systems indicated excellent intrarater reliability (K = 0.81, K-w = 0.83; K = 0.798, K-w = 0.82). This trial is registered with Clinicaltrials.gov, under number NCT03559296. Conclusions: Based on the findings of this study, SEG and SEFS demonstrated acceptable reliability. SEG and SEFS appear to be reliable and useful grading systems for the assessment of breast cancer-related lymphedema.
Keywords: arm; breast cancer; echogenicity; lymphedema; subcutaneous tissue; ultrasound; CLINICAL MEASURES; SEVERITY; ULTRASONOGRAPHY; ULTRASOUND; VOLUME